Making the Malaysian University-of-the-Future relevance in the digital era: improving the wellbeing of B40 youth in Tanzania through digital entrepreneurship education and International Community Engagement Programs - Mustafa Hassan, Muhsin; Ahmad Dahlan, Abdul Rahman (www.researchpublish.com, 2021)
Unemployment is the one of the major challenges faced many countries around the globe, the large part of the problem can be seen in youth. Tanzania as a developing country and a member of UN faced a vital challenge of youth unemployment. It is generally assumed that the Higher learning institution produce graduate with the mismatch skills and knowledge as compared to the demand of the current job markets. The advancement of technology can renovate the traditional educational system into the university-of-the future that can produce the balance graduate through the utilization of digitizing entrepreneurship education program and community engagement that can facilitate the problem unemployed graduate youth and improve their well-being. The paper is adopting design thinking approach in developing business model of UotF. BMC and VPC models utilized to ideating and formulating the conceptual business model that harness the digital capability and community engagement in improving the well-being of B40 Youth in Tanzania. The approach includes conducting interviews and literature reviews for understanding the needs, challenges and key problems. The objective is to enhance the well-being B40 unemployed youth with skills sets required for decent jobs and stimulate the economic growth through DEEP CE.